How we read the Bible : a guide to scripture's style and meaning - Vermeulen, Karolien; Hayes, Elizabeth R. (Elizabeth Russell), 1952- (Grand Rapids, MI. W.B. Eerdmans Publishing Company, 2022)
"A handbook on reading the Bible that explores the interaction between the cues of the text and the context of the reader through key stylistic elements"--
"The Bible is interpreted in a variety of ways and through a myriad of lenses. But how we interpret Scripture depends first of all on how we read it. This handbook focuses on the process of reading itself, taking a cognitive-stylistic approach grounded in recent research on language and the mind. Through accessible explanations of twelve key stylistic elements, How We Read the Bible provides all who study Scripture with the tools to understand what happens when we read and draw meaning from biblical texts. Rather than problematizing the divide between authors from the ancient world and a modern-day audience, Karolien Vermeulen and Elizabeth Hayes bridge the gap by exploring the interaction between the cues of the text and the context of the reader. With numerous examples from the Old and New Testaments and helpful suggestions for further study, How We Read the Bible can be used within any framework of biblical study-historical, theological, literary, and others-as a pathway to meeting Scripture on its own terms"--
Includes bibliographical references and index.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Language, style; Bible -- Hermeneutics; RELIGION / Biblical Studies / Exegesis & Hermeneutics; LITERARY CRITICISM / Ancient & Classical